Killing them softly: Ontogeny of jaw mechanics and stiffness in mollusk‐feeding freshwater stingrays. (5th April 2019) - Rutledge, Kelsi M.; Summers, Adam P.; Kolmann, Matthew A.
Abstract: Durophagous predators consume hard‐shelled prey such as bivalves, gastropods, and large crustaceans, typically by crushing the mineralized exoskeleton. This is costly from the point of view of the bite forces involved, handling times, and the stresses inflicted on the predator's skeleton. It is not uncommon for durophagous taxa to display an ontogenetic shift from softer to harder prey items, implying that it is relatively difficult for smaller animals to consume shelled prey. Batoid fishes (rays, skates, sawfishes, and guitarfishes) have independently evolved durophagy multiple times, despite the challenges associated with crushing prey harder than their own cartilaginous skeleton. Potamotrygon leopoldi is a durophagous freshwater ray endemic to the Xingu River in Brazil, with a jaw morphology superficially similar to its distant durophagous marine relatives, eagle rays (e.g., Aetomylaeus, Aetobatus ). We used second moment of area as a proxy for the ability to resist bending and analyzed the arrangement of the mineralized skeleton of the jaw of P. leopoldi over ontogeny using data from computed tomography (CT) scans. The jaws of P. leopoldi do not resist bending nearly as well as other durophagous elasmobranchs, and the jaws are stiffest nearest the joints rather than beneath the dentition. While second moment has similar material distribution over ontogeny, mineralization of the jaws under the teeth increases with age. Neonate rays have low jaw stiffness and poor mineralization, suggesting that P. leopoldi may not feed on hard‐shelled prey early in life. These differences in the shape, stiffness and mineralization of the jaws of P. leopoldi compared to its durophagous relatives show there are several solutions to the problem of crushing shelled prey with a compliant skeleton. Abstract : Changes to jaw stiffness over ontogeny suggest durophagous freshwater rays cannot consume shelled prey as juveniles. Contrary to other molluscivorous batoids, jaws are more robust and internally supported at the joints than under the teeth.